Transformation of Print Media Management Into Online Media (Case Study on Bengkulu Ekspress Daily Media) - Reko Muhardi; Alfarabi Alfarabi; Sonde Martadireja (Publikasi Indonesia, 2024)
This study examines the management transformation process carried out by print media in switching to online media platforms. The research focuses on understanding media management carried out by print media in adapting information technology and its content into the online realm. Qualitative research methods were used, including an in-depth interview with the editor-in-chief of Media Harian Bengkulu Ekspress, which has transformed into online media. Data analysis was carried out to determine the management changes made by the Bengkulu Ekspress Daily media when switching to online media. The results highlight the transformation of media management of Bengkulu Ekspress Daily, starting from the formation of a special team that handles this online media itself, changes in news language that follow the tastes of the community, adjustments to the layout on the web, and interaction with readers through communication media. The implications of this transformation show significant changes in business models as well as increased reader engagement through online platforms